動物に関する日本とインドネシアのことわざの比較: ジャカルタ国立大学における会話授業へのことわざの含意 - Yuniarsih (Universitas Negeri Jakarta, 2017)
Even though the meanings are similar, some mammals used in the proverb are different. In this research, I was surveyed in